Peningkatan Brand Awareness Dengan Pemanfaatan Digital Marketing Pada UMKM “RKT Kitchen” - Cynarawita Firjatullah; Sonja Andarini (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Low competitiveness is usually caused by the inadequate ability to sell business actors. Thus, the purpose of this service is to increase MSMEs actors' understanding of the value of digital media for marketing and to build product identity through training and mentoring. UMKM RKT Kicthen in Rungkut Asri, Surabaya, became partners for this activity. By providing training in the form of Digital Marketing outreach, registering business locations on Gmaps, product photos, logo and packaging designs and product catalogs. The results of this community service project show that RKT Kicthen MSMEs actors receive education about the need to market products using digital media. Through training and mentoring it is expected to be able to increase Brand Awareness so that MSME actors can expand their market and competitiveness in utilizing Digital Marketing.